A study of pressure characteristics of methane explosion in a 20 m buried tunnel and influence on structural behaviour of concrete elements. (April 2021) - Meng, Qingfei; Wu, Chengqing; Li, Jun; Wu, Pengtao; Xu, Shenchun; Wang, Zhongqi
Highlights: An experimental study of methane gas explosion in a 20 m buried tunnel is conducted. The explosion pressure distribution in the tests is non-uniform. The captured pressure peaks are similar to those in vented gas explosion. Concrete specimens demonstrated minor cracks on both interior and exterior surfaces. Abstract: With increasing use of natural gas in urban metropolitan areas, utility tunnels that contain utility and gas lines have become critical infrastructure. A leak within a gas pipe may cause methane-air explosions in the tunnel, leading to structural damage and casualties. Thus, it is necessary to investigate the response of structural members against explosion loads in the tunnel. Few studies in the open literature have studied the effects of a methane-air explosion in a full-scale concrete tunnel. This study presents two 9.5% methane-air explosions in a tunnel with a dimension of 20000 mm × 1800 mm × 600 mm. The pressure characteristics are summarized and compared with existing pressure–time curve of the methane-air explosion in typical vented containers. Similarities of pressure characteristics between the current study and previous studies avaliable from the literature are identified. Apart from explosion pressure characteristics, concrete structural specimens with a dimension of 1800 mm × 400 mm × 90 mm are also investigated. Geopolymer concrete, ultra high performance concrete (UHPC) and conventional concrete with compressive strength of approximately 70 MPa, 150 MPa and 30 MPa, respectively, were used to manufacture the testing specimens subjected to the methane-air explosions in the tunnel. In this study, the cracks were observed on all specimens. Due to large size of the tunnel and gas leakage during blast, the pressure distribution in the tunnel is not as uniform as observed in methane-air explosion chamber from the previous literatures. The conventional concrete specimen positioned between two pressure sensors is selected to validate the numerical model in the present study. The calibrated numerical model is then used to study the structural responses of concrete specimen subjected to the captured pressure.